Hematological and Inflammatory Parameters in Hookah Smokers and Nonsmokers: A Cross-sectional Study. - Sidra Latif; Muniza Saeed (University of Lahore, 2022)
Objective: To observe the effects of hookah smoking on hematological and inflammatory parameters in chronic hookah smokers. Methods: A cross sectional observational study was conducted in the setting of Post Graduate Medical Institute, Lahore from March to September, 2021, on 30 male chronic hookah smokers, who had been smoking hookah for more than 5 years, in the age range of 30-60 years and a comparison of their hematological parameters was done with 30 subjects of the same age group and ethnic background with no history of hookah smoking. Fresh blood samples from antecubital vein were collected and tested for hemoglobin (Hb) content, red blood cells (RBC) count, packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC), platelet count, neutrophil count, lymphocyte count and neutrophil lymphocyte ratio (NLR). An automatic hematological analyzer was used to get results. High sensitivity CRP (hs-CRP) was measured using Elisa kit.  Data was analyzed using SPSS 21. Results: A statistically significant difference was found in Hb, PCV, MCV, MCH, MCHC, platelets, MPV (p ˂ 0.05). Inflammatory markers such as hs-CRP (p = 0.05), NLR (p = 0.03) were significantly higher in hookah smokers as compared to non-smoker. Conclusion: Hookah smokers have altered hematological and inflammatory parameters and are at higher risk of developing atherosclerosis, cardiovascular and pulmonary diseases associated with these alterations.